2D Materials‐Based Thermal Interface Materials: Structure, Properties, and Applications - Dai, Wen; Wang, Yandong; Li, Maohua; Chen, Lu; Yan, Qingwei; Yu, Jinhong; Jiang, Nan; Lin, Cheng‐Te (Advanced materials (Weinheim), 2024)
The challenges associated with heat dissipation in high‐power electronic devices used in communication, new energy, and aerospace equipment have spurred an urgent need for high‐performance thermal interface materials (TIMs) to establish efficient heat transfer pathways from the heater (chip) to heat sinks. Recently, emerging 2D materials, such as graphene and boron nitride, renowned for their ultrahigh basal‐plane thermal conductivity and the capacity to facilitate cross‐scale, multi‐morphic structural design, have found widespread use as thermal fillers in the production of high‐performance TIMs. To deepen the understanding of 2D material‐based TIMs, this review focuses primarily on graphene and boron nitride‐based TIMs, exploring their structures, properties, and applications. Building on this foundation, the developmental history of these TIMs is emphasized and a detailed analysis of critical challenges and potential solutions is provided. Additionally, the preparation and application of some other novel 2D materials‐based TIMs are briefly introduced, aiming to offer constructive guidance for the future development of high‐performance TIMs. This review delves into high‐performance thermal interface materials (TIMs) based on 2D materials like graphene/boron nitride, pivotal for heat management in advanced electronics. Focusing on their structural attributes, properties, and applications, it differentiates from other reviews by emphasizing their developmental history, addressing critical challenges, and proposing solutions. Additionally, it introduces other 2D materials‐based TIMs, providing insights for future advancements.